Failure Mechanism of Salt Barrier in Saline Soil Subgrade in Cold and Arid Plateau Areas - Yurong Zhang; Wen Zhang; Yanbin Fan; Shiyi Liu; Yunxiu He; Yi Zou (Advances in Civil Engineering)
In traffic engineering design in saline soil environments, a salt barrier is usually installed in the embankment to prevent secondary salinization damage on the upper embankment and road surface. However, using this salt barrier method in saline soil subgrade projects in cold and arid highland areas has led to the problem of salt barrier failure, and the failure mechanism remains unclear. The study was performed in the saline soil distribution area in the Qaidam Basin on the northeastern part of the Qinghai–Tibet Plateau. We collected samples from the natural saline soil foundation and the structural layer of the subgrade soil using the method of excavating a road section that had undergone salt barrier failure. Laboratory tests and theoretical calculations were carried out on the particle gradation of the natural saline soils and the structural subgrade soil layers. In addition, their water and salt transport heights and the failure mechanism of the subgrade salt barrier were studied. The results showed that salt chemistry increases the capillary force between the soil grains in highly saline soil environments. This increases the water–salt transport of more than 850.00 mm in saline soils, which is much greater than the capillary water rise in ordinary soils (463.0–650.0 mm). When no water barrier geotextile layer is set in the subgrade structure, there is frequently a high headwater and salt transport in the soil layer of the subgrade structure for a long time. There is continuous vapor and salt transport in the large pores of the coarse-grained salt barrier. The vibration load of the road surface causes the fine soil particles to migrate downward into the coarse-grained salt barrier, reducing the thickness of the salt barrier. Under the combined effect of these three effects, the salt barrier of the saline soil subgrade in cold and arid areas fails to resist salt migration, and the subgrade is prone to secondary salinization.